The Effect Of Liquidity And Profitability On Share Prices In Telecommunication Companies Listed On The Indonesia Stock Exchange For The 2018-2022 Period - Sururi Maudhunati; Ahmad Rodoni; Muhammad Rasyid Ridlo (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study is to determine the effect of Liquidity (Current Ratio) and Profitability (Return On Assets) on share prices in Telecommunication Companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. The method used is descriptive analysis with a quantitative approach, then the selection of a feasibility test model is carried out, namely the hausman test, followed by hypothesis testing using the Bergand linear regression analysis test. The source of this research data was obtained from www.idx.co.id in the form of secondary data. The sampling technique used is purposive sampling technique. The data was then analyzed using panel data regression with the Eviews 12 program. Based on the results of data analysis, it is concluded that the liquidity variable (CR) has a negative and insignificant influence on stock prices. While the variable profitability (ROA) has a positive and significant influence on the variable stock price. From the results of simultaneous data, it can be concluded that liquidity (CR) and probability (ROA) have a significant influence on the share price of Indonesian Telecommunication companies listed on the IDX during the 2018-2022 period.